2015
DOI: 10.1007/s00705-015-2665-y
|View full text |Cite
|
Sign up to set email alerts
|

Noncytopathic bovine viral diarrhea virus 2 impairs virus control in a mouse model

Abstract: Bovine viral diarrhea virus (BVDV) is an economically important pathogen that causes development of mild to severe clinical signs in wild and domesticated ruminants. We previously showed that mice could be infected by BVDV. In the present study, we infected mice intraperitoneally with non-cytopathic (ncp) BVDV1 or ncp BVDV2, harvested the blood and organs of the infected mice at days 4, 7, 10 and 14 postinfection (pi), and performed immunohistochemical analyses to confirm BVDV infection. Viral antigens were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
2
6
0
1
Order By: Relevance
“…The difference in virulence between the two strains was evidenced by an earlier onset of viremia in the mice infected with the NY-93 strain than in those bearing the 98-124 strain, and by the induction of a peak of systemic TNF-α in all the animals infected with 98-124. None of the infected mice developed clinical disease, coincident with previous reports (26,41); with the infection being verified by only the presence of viremia, both by virus titration and RT-PCR.…”
Section: Discussionsupporting
confidence: 88%
“…The difference in virulence between the two strains was evidenced by an earlier onset of viremia in the mice infected with the NY-93 strain than in those bearing the 98-124 strain, and by the induction of a peak of systemic TNF-α in all the animals infected with 98-124. None of the infected mice developed clinical disease, coincident with previous reports (26,41); with the infection being verified by only the presence of viremia, both by virus titration and RT-PCR.…”
Section: Discussionsupporting
confidence: 88%
“…In the distribution of viral antigens, the previous study (20) showed that viral antigens were detected in the spleen of all infected mice from days 4 through 14 of post-infection and suggested that the spleen is the most reliable tissue for BVDV antigen detection in a murine model. In the present study, we found that viral antigens were consistently detected in both the spleen and blood.…”
Section: Discussionmentioning
confidence: 93%
“…Fifteen mice were assigned into the CP BVDV-, NCP BVDV-, and mock-infection groups with 5 mice per group. Challenge was performed by intraperitoneal (IP) injection of 0.4 mL of culture medium containing 10 6 copies/mL of each virus ( 20 ). Mock-infected mice were given 0.4 mL of DMEM (Gibco, Grand Island, NY, USA) via IP injection.…”
Section: Methodsmentioning
confidence: 99%
“…En un primer experimento, dos grupos de 8 ratones BALB/c (hembras, 6-8 semanas de vida) fueron inoculados por vía intra-peritoneal (IP) con 0,4 ml de una dosis de 5.10 5 DICT50/ml de dos cepas del VDVB. Esta dosis fue la establecida por Seong y colaboradores en su trabajo de puesta a punto de este modelo [144]- [146]. Cuatro animales se dejaron como control sin infectar, y solamente recibieron 0,4 ml de medio de infección.…”
Section: Resultados Desarrollo Del Modelo Murino De Infección Por El unclassified